SIFAT PENGOLAHAN DAN SIFAT FISIK PULP SEMBILAN JENIS KAYU DARI INDONESIA BAGIAN TIMUR - Setyani B; Lestari Lestari; Yoswita Yoswita (Jurnal Penelitian Hasil Hutan, 2003)
This  paper  dealt  with  chemical  processing  and  physical  properties  of  wood  for  pulp  of  nine  woods.  The  analyses  consisted  of  pulp  screen  yield,  alkali  consumption,  permanganate    number,  breaking  length,  and  tearing  factor.  This  analysis  is  very  important  in  determining  the  suitability  of  wood  species  as  raw  material  for  pulp  paper  production.Results  of  chemical  pulping  process  indicated  that  pulp  screen  yield  in  a  range  of  32.70  -  47.71  %,  alkali  consumption  12.20  -  15.50  %,  permanganate  number  9.75  -  20.70,  breaking  length  value  2.60  -  4.40  km,  bursting  factor  27.51  -  51.27,  tearing  factor  74  -  132,  and  folding  endurance  4.5  -  59.5  df.  The  results  revealed  that  all  wood  species  were  suitable  for  pulp  and  paper  production.  Chemical  processing  of  these  wood  species  produced  high  pulp  screen  yield,  low  alkali  consumption,  pulp  easily  bleached  pulp  and  good  physical  pulp  properties.  Two  of  the  species,  Horsfieldia  sylvetris  Warb  and  Calophyllum  inophyllum  L.  resulted  in  the  best  quality  of  pulp.